História da Escola Normal do Colégio Providência de Mariana – MG (1902 - 1930) - Silva, José Gustavo Almeida da (2017)
The current work is inserted in the investigations proposed at the History of the Education field, following the researches refered to the History of Institutional Education. The object of our analysis is the Normal School of the Colégio Providência, that was located in the city of Mariana – MG, covering its existence at the first decades of the twentieth century, between the years of 1902 (time of its inauguration) and 1930 (when its facilities were broadened and modified), therefore, this research is inserted at the historical period called The First Republic of Brazil, covering the years of 1889 and 1930. The normal school was created by the Sisters Daughters of Charity of St. Vincent de Paul and inserted into the Colégio Providência headquarters, a school institution that already functioned in Mariana since the middle of nineteenth century. The normal school focuses on women’s education, as well as the primary school directed by this congregation. The work will present the means by which this institution performed the role of teachers training, based on catholic ideals, as well as in the model of education already used in the primary course: the vincentian pedagogy. As a guideline, we have the analysis of the project stablished for the Normal School at the beginning of the Republic period, along with intense educational reforms on the first decades of the twentieth century, period that was at its height through the consolidation of the position of this institution as the main reference on teacher’s training. The research have been oriented by a bibliography related to the themes approached and by the data collected in primary (inside the normal school) and secondary (periodicals, decrees, laws, reports) documents from the comprehension of the historical context and historical-educational period in which this institution operates, organizing itself from a more expanded conception (national, interstates) to get into the particular field (regional, municipal, institutional), focusing at the local specificities to better understand them in their complexity, also placing them in reference to the national education context of the beginning of the republican period.